An enhanced system resilience assessment method during seismic hazards: Incorporating the iteration algorithm and impact increment state enumeration - Changle Liu; Baohong Li; Qin Jiang; Yingmin Zhang; Tianqi Liu (International Journal of Electrical Power & Energy Systems)
In recent years, seismic hazards have become increasingly frequent and severe, presenting significant threats to the resilience of large-scale power systems. It is unclear when seismic hazard will occur, and this complicates the quantification of transmission line failure probability, while the uncertainty inherent in the cascading failure process poses challenges for calculating resilience metrics. Meanwhile, the exponentially increasing number of enumerations associated with a rise in failure order introduces computational challenges when we seek to assess system resilience. To address these critical challenges, this paper presents a resilience assessment framework for accurately evaluating power system resilience during seismic hazards. The proposed framework includes a transmission line failure probability model, an interval estimation method for handling uncertainties in cascading failures, and an improved enumeration algorithm. This improved algorithm, Upper-Lower- Bound Iteration Impact Increment State Enumeration, integrates the Impact Increment State Enumeration (IISE) with an upper- and lower-bound iteration to enhance computational efficiency.The interval estimation method allows for resilience estimation by evaluating both the best and worst system performance cases in uncertain cascading failures. Additionally, the failure probability of transmission lines is quantified by decomposing the influencing factors. The effectiveness of the proposed method is validated using the IEEE 118-bus system, with further validation conducted on a practical 500 kV system, and the results are presented herein.